Construction of an In Vivo Nonsense Readthrough Assay System and Functional Analysis of Ribosomal Proteins S12, S4, and S5 in Bacillus subtilis - Inaoka, Takashi (American Society for Microbiology, 2001)
To investigate the function of ribosomal proteins and translational factors in Bacillus subtilis, we developed an in vivo assay system to measure the level of nonsense readthrough by utilizing the LacZ-LacI system. Using the in vivo nonsense readthrough assay system which we developed, together with an in vitro poly(U)-directed cell-free translation assay system, we compared the processibility and translational accuracy of mutant ribosomes with those of the wild-type ribosome. Like Escherichia coli mutants, most S12 mutants exhibited lower frequencies of both UGA readthrough and missense error; the only exception was a mutant (in which Lys-56 was changed to Arg) which exhibited a threefold-higher frequency of readthrough than the wild-type strain. We also isolated several ribosomal ambiguity (ram) mutants from an S12 mutant. These ram mutants and the S12 mutant mentioned above (in which Lys-56 was changed to Arg) exhibited higher UGA readthrough levels. Thus, the mutation which altered Lys-56 to Arg resulted in a ram phenotype in B. subtilis. The efficacy of our in vivo nonsense readthrough assay system was demonstrated in our investigation of the function of ribosomal proteins and translational factors.